Knocking down GALNT6 promotes pyroptosis of pancreatic ductal adenocarcinoma cells through NF-κB/NLRP3/GSDMD and GSDME signaling pathway - Ding, Mengyang; Liu, Jingyu; Lv, Honghui; Zhu, Yanlin; Chen, Yumiao; Peng, Hui; Fan, Sairong; Chen, Xiaoming (Frontiers in Oncology, 2023)
Background Pancreatic ductal adenocarcinoma (PDAC), the most prevalent type of pancreatic cancer, is a highly lethal malignancy with poor prognosis. Polypeptide N-acetylgalactosaminyltransferase-6 (GALNT6) is frequently overexpressed in PDAC. However, the role of GALNT6 in the PDAC remains unclear. Methods The expression of GALNT6 in pancreatic cancer and normal tissues were analyzed by bioinformatic analyses and immunohistochemistry. CCK8 and colony formation were used to detect cell proliferation. Flow cytometry was applied to detect cell cycle.The pyroptosis was detected by scanning electron microscopy. The mRNA expression was detected by qRT-PCR. The protein expression and localization were detected by western blot and immunofluorescence assay. ELISA was used to detect the levels of inflammatory factors. Results The expression of GALNT6 was associated with advanced tumor stage, and had an area under curve (AUC) value of 0.919 in pancreatic cancer based on the cancer genome atlas (TCGA) dataset. Knockdown of GALNT6 inhibited cell proliferation, migration, invasion and cell cycle arrest of PDAC cells. Meanwhile, knockdown of GALNT6 increased the expression levels of interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and interleukin-18 (IL-18), the release of inflammasome and an increasing of Gasdermin D (GSDMD), N-terminal of GSDMD (GSDMD-N), Gasdermin E (GSDME) and N-terminal of GSDME (GSDME-N) in PDAC cells. GALNT6 suppressed the expression of NOD-like receptor thermal protein domain associated protein 3 (NLRP3) and GSDMD by glycosylation of NF-κB and inhibiting the nucleus localization of NF-κB. Additionally, GALNT6 promotes the degradation of GSDME by O-glycosylation. Conclusion We found that GALNT6 is highly expressed in pancreatic cancer and plays a carcinogenic role. The results suggested that GALNT6 regulates the pyroptosis of PDAC cells through NF-κB/NLRP3/GSDMD and GSDME signaling. Our study might provides novel insights into the roles of GALNT6 in PDAC progression.